Social, Cultural, and Local Contexts in PAI - Ghina, Ghina Sofia Mahfuzah; Ani Cahyadi (The Future of Education Journal, 2026)
This study examines the integration of local wisdom into Islamic Religious Education (PAI) to enhance its relevance in addressing the challenges posed by Indonesia's diverse socio-cultural context. The primary aim of this research is to analyze the importance of incorporating local values into the PAI curriculum design to strengthen character development, promote cultural identity, and ensure that Islamic teachings are understood in a way that resonates with students' lived experiences. This research uses a qualitative approach, including literature reviews and case studies, to explore the application of local wisdom such as the phrase "Kayuh Baimbai," which teaches the importance of cooperation, "Gotong Royong," which emphasizes community solidarity, and the principles of adab bedamai, which promote tolerance and mutual respect. Additionally, the expressions "Apik-apik kalu tabarusuk" remind us to be cautious in receiving information, "Banganga dahulu hanyar baucap" encourages thinking before speaking, and "Bila wani menimbai lunta, wani tu manajuni" teaches responsibility for every action taken. The findings of the study show that integrating local cultural values into PAI can increase student engagement, deepen moral teachings, and create a learning environment that values diversity. However, the study also reveals several challenges, such as the potential misinterpretation of cultural values and varying levels of teacher competence in delivering contextually relevant content. In conclusion, this study advocates for a balanced approach in teaching PAI that harmonizes religious teachings with Indonesia's rich cultural heritage.